2022
DOI: 10.1002/cam4.5364
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different methods of obturator nerve block in transurethral resection of bladder tumors: A systematic review and network meta‐analysis

Abstract: Background: Bladder cancer is the most common malignancy of the urinary system, and accounts for 3% of newly diagnosed tumors. Transurethral resection of bladder tumor plays a key role in treating bladder cancer, among which one of the most serious complications is bladder perforation caused by obturator nerve reflex. Obturator nerve reflex can be prevented by inducing obturator nerve block after lumbar anesthesia. However, No study so far has compared the inhibitory effect of different obturator nerve block a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…Perioperative bleeding was observed in only one patient in the ultrasound-guided ONB group and 3 patients in blind group. Our ndings are consistent with a recent meta-analysis by Wu et al [14]. The authors reported that ultrasoundguided technique was the optimum approach in terms of preventing bladder perforation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Perioperative bleeding was observed in only one patient in the ultrasound-guided ONB group and 3 patients in blind group. Our ndings are consistent with a recent meta-analysis by Wu et al [14]. The authors reported that ultrasoundguided technique was the optimum approach in terms of preventing bladder perforation.…”
Section: Discussionsupporting
confidence: 92%
“…In a very recent meta-analysis, various ONB approaches were compared in terms of preventing ON re ex and related complications. ONB performed with nerve stimulator was found to be superior to ultrasound-guidance or blind technique in preventing muscle contractions [14]. Despite this result, ultrasound-guidance has become very popular in regional anesthesia practice in the last decade by providing practical, time-saving procedures for clinicians when compared to using a nerve-stimulator.…”
Section: Discussionmentioning
confidence: 99%